The role of occult spinal malformation and upper urinary tract deterioration in children with intractable voiding dysfunction - (:unkn) unknown (MARMARA UNIV, FAC MEDICINE, 2017)
Objectives: To evaluate the presence of upper urinary tract deterioration (UUTD) and accompanying pathologies in children treated with the diagnosis of non-neurogenic bladder-sphincter dysfunction (NNBSD). Patients and Methods: We retrospectively reviewed the medical records of 316 consecutive patients with NNBSD who were treated. All cohort were grouped into two: Group I (Treatment success; n=284), Group II (Treatment failure with any form of occult spinal pathology; n=32). Thirty-four children with treatment-failure and normal magnetic resonance imaging (MRI) findings were excluded. Groups were compared for pre- and post-treatment pediatric lower urinary tract symptom score (PLUTSS), presence of UUTD and urodynamic findings. Results: The mean PLUTSS was significantly less in Group I compared with Group II at pre-treatment and 3 months thereafter the initial treatment (12.20 +/- 5.90 and 5.20 +/- 4.90 vs 20.3 +/- 2.14 and 18 +/- 3.4, respectively p<0.01). The mean cystometric capacities and detrusor leak point pressure (DLPP) of Group II prior to initial treatment and after 6 months of the untethering surgery were found to be 194, 267 mL and 28, 12cm H2O, respectively (p<0.05). Presence of UUTD was significantly correlated with DLPP >20 cm H2O and presence of vesicoureteral reflux (VUR). Conclusion: UUTD in NNBSD is more common in children with occult spinal pathology, than in those without.
Keywords: Non-neuropathic bladder sphincter dysfunction; Upper urinary tract deterioration; Symptom score